Tinjauan Pelepasan Informasi Rekam Medis Kepada Pihak Ketiga Di RSU Imelda Pekerja Indonesia Medan - Erlindai Purba; Hesty Afriani Sidabutar (Jurnal Ilmiah Perekam dan Informasi Kesehatan Imelda, 2021)
The Imelda Workers General Hospital of Indonesia does not yet have specific routines regarding the release of medical record information to third parties. however, they have used regular procedures for providing information and borrowing medical records in general, This study aims to determine the number of requests for medical record information. This type of research is descriptive, namely the research method carried out with the aim of making an objective state. The population was 4 people and the sample size was 4 people as the total sampling with the research methodology using quantitative methods. How to collect data by interview and observation. The results showed that the services of the Imelda Hospital for Indonesian Workers in Medan according to legalized death certificates amounted to 34 percent (0.56%), claims for raharja services amounted to 56 percent (0.92%), audits and insurance claims were 69 percent (1.14%) , research or education as much as 54 percent (0.89), post mortem as much as 28 percent (0.46%), BPJS as much as 5,790 percent (99.00%). Based on the results of the study, it is known that knowing the data on the number of requests for medical record information in January-June 2020 is 6,224 with a percentage (99.97%). As well as the absence of a special SPO on procedures and utilization of medical record information of deceased patients, however, they have used the permanent procedure of providing information and borrowing medical records in general. It is recommended that hospitals and medical record officers provide regular training or coaching to officers. And to health workers, especially medical records, in order to maintain the confidentiality of patient medical record information and carry out the established procedures properly.